(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The Purpose Of This Study Was To Explain The Behavior Of The Pamong Praja Police Unit In The Service Of Order In The Glorious Peak Distrct Data Collection Uses Interview Documentation While Data Analysis Techniques Are Carried Out Through The Stages Of Data Colletion Editorial Data Presentation Data Based On The Results Of Data Analysis Concluded That The Behavior Of In Order Service In The High Peak Ditricts Of Papua Proince Observed From Two Criteria Namely Preventive And Repressive Yet Maximizing Public Service Based On The Results Of The Study It Was Found That The Behavior Of The Civil Service Unit In Service Had Not Been Maximized So That They Could Recommend Advice The Quality Of Human Resources Head Of Civil Service Police And Pol Pp Members Need To Be Increased Through Government Regulation Number 6 Years In 2014 , Civil Service Police Unit Explaind That The Civil Service Police Unit Was Part Of The Regional Apparatus In The Enforcement Of The Regional Regulations To Carry Out Public Order And The Peace Of The People At The Level So That There Was No Misunderstanding Between The Government And Other Communities Regulated In The Government Petrifiend The Head Of State By Refreshing Public Service Article 86 Of Law Number 5 Of 1974 Which Was Formed By District Civil Service Police Unit ,The Peak Of Which Failed On May 9 1992 Whose Members Consist Of A Combination Of Members Of Public Order And Task Forces Managing Urban Areas Key Words : Behavior Of The Civil Service Police Init Order Service